Gearing health systems for universal health coverage - Cerf, Marlon E. (Frontiers in Health Services, 2023)
Universal health coverage requires adequate and sustainable resourcing, which includes human capital, finance and infrastructure for its realization and sustainability. Well-functioning health systems enable health service delivery and therefore need to be either adequately or optimally geared prepared and equippedfor service delivery to advance universal health coverage. Adequately geared health systems have sufficient capacity and capability per resourcing levels whereas optimally geared health systems achieve the best possible capacity and capability per resourcing levels. Adequately or optimally geared health systems help to mitigate health system constraints, challenges and inefficiencies. Effective, efficient, equitable, robust, resilient and responsive health systems are elements for implementing and realizing universal health coverage and are embedded and aligned to a global people-centric health strategy. These elements build, enhance and sustain health systems to advance UHC. Effective and efficient health systems encompass continuous improvement and high performance for providing quality healthcare. Robust and resilient health systems provide a supportive and enabling environment for health service delivery. Responsive and equitable health systems prioritize people and access to healthcare. Efforts should be made to design, construct, redefine, refine and optimize health systems that are effective, efficient, equitable, robust, resilient and responsive to deliver decent quality healthcare for all.